Acute appendicitis causing small intestinal band obstruction in a premature baby: A case report - Iftikhar Ahmad Jan; Sarah Bin Hariz; Faisal Al Zidgali; Zahid Latif Saqi; Ghazy Habeeb Lutf (EL-Med-Pub, 2020)
Background: Bilious vomiting is a common symptom of neonatal intestinal obstruction. The etiology is mostly related to congenital anomalies and other conditions causing intestinal obstruction. Case Presentation: We report a case of a seven days male premature baby (35 Weeks) that presented with features of intestinal obstruction including bilious vomiting and abdominal distention. X-ray abdomen showed features of complete small bowel obstruction. On laparotomy, the baby had acute appendicitis causing multiple adhesions, and an adhesion band was responsible for intestinal obstruction. Adhesions were divided, and appendectomy performed. Postoperatively the baby had an uneventful recovery and was discharged in a stable condition. Conclusion: Neonatal appendicitis causing intestinal obstruction is a rare phenomenon and should be considered in the differential diagnosis of babies presenting with bilious vomiting.